The Effect Of The Stad-Type Cooperative Learning Model Through The Paikem Approach On The Character And Learning Outcomes Of Fourth-Grade Students At SDN - Shinta Indriani Sakina; Abrina Maulidnawati Jumrah; A. Resky Nurhidayah (ALENA : Journal of Elementary Education, 2026)
This lstudy laims lto ldetermine lthe leffect lof lthe lSTAD-type lcooperative llearning lmodel lthrough lthe lPAIKEM lapproach lon lthe lcharacter land llearning loutcomes lof lfourth-grade lstudents lat lSDN l143 lInpres lLeko. lThe lresearch lemployed la lquantitative lmethod lwith la lQuasi-Experimental lDesign, linvolving l40 lstudents las lthe lsample lwho lwere ldivided linto lan lexperimental lgroup land la lcontrol lgroup. lData lwere lcollected lthrough lobservation lsheets, llearning loutcome ltests, land ldocumentation, land lwere lanalyzed lusing ldescriptive land linferential lstatistics. lThe lresults lshowed lthat lthe limplementation lof lthe lSTAD llearning lmodel lthrough lthe lPAIKEM lapproach lwas lcarried lout leffectively land lwas lable lto lenhance lstudents’ lcharacter, lmaking lthem lmore lactive, lcreative, ldisciplined, lresponsible, land lconfident. lIn laddition, lthe lapplication lof lthis lmodel lhad la lpositive leffect lon lstudents’ llearning loutcomes, las lindicated lby lthe limprovement lin lposttest lscores lcompared lto lpretest lscores. lOverall, lthis llearning lmodel lnot lonly limproves lstudents’ lacademic labilities lbut lalso lsupports lcharacter ldevelopment. lBased lon lthese lfindings, lthe lresearcher lrecommends lthat lteachers lconsistently limplement lthe lSTAD lmodel lwith lthe lPAIKEM lapproach lin lteaching land llearning lactivities, lschools lprovide ltraining land lsupporting lfacilities lfor lteachers, land lparents lsupport lcooperative-based llearning lat lhome lto lstrengthen lstudents’ lcharacter land llearning loutcomes.